2018
DOI: 10.1007/s11869-018-0638-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of TEOM monitors for continuous long-term sampling of ambient particles for analysis of constituents and biological effects

Abstract: Many countries have implemented exposure limits for the concentration of ambient particular matter and do therefore have to monitor their concentration. This could be performed with TEOM monitors (Tapered Element Oscillating Microbalancemonitors) that contain a filter on which particles are collected. These filters are regularly exchanged for new ones. The aim of this study was to test the feasibility of collecting used filters from monitors at different locations and establishing a method to extract particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…During the summer, the particle levels are relatively low, indicating the importance of analysing also what the particles carry on their surface. These results confirm the previous study (Nosratabadi et al 2019) and are realistic since at this time of the year, when it is warm and humid, conditions are particularly beneficial for bacterial growth (Fig. 1e).…”
Section: Endotoxinssupporting
confidence: 92%
See 4 more Smart Citations
“…During the summer, the particle levels are relatively low, indicating the importance of analysing also what the particles carry on their surface. These results confirm the previous study (Nosratabadi et al 2019) and are realistic since at this time of the year, when it is warm and humid, conditions are particularly beneficial for bacterial growth (Fig. 1e).…”
Section: Endotoxinssupporting
confidence: 92%
“…The earlier study showed that the particle masses peaked in March/April while the oxidative capacity of the particles was at its highest early in the spring and the content of endotoxins and the pro-inflammatory response were highest in late summer. This indicates that the source and composition of the particles are different over the year and may pose different health risks (Nosratabadi et al 2019). In the present study, a more in-depth analysis of TEOM filters collected monthly in three cities in the southeast part of Sweden are presented.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations